INFLUENCE OF ORGANIZATIONAL CULTURE ON EFFECTIVENESSPERFORMANCE OF EMPLOYEES AT THE GRADUATE OF HASANUDDIN UNIVERSITY - Andi Noorhayati Amirullah; Nurasia Natsir; A,M Fadli Mappisabbi (Universitas Veteran Bangun Nusantara, 2022)
The Influence of Organizational Culture on the Effectiveness of Employee Performance at Hasanuddin University, this study aims to determine whether there is an influence between organizational culture on the effectiveness of employee performance, as well as to determine the role of cultural influences on the effectiveness of the performance of postgraduate employees at Hasanuddin University. This study used a qualitative research method with a descriptive approach, while the data collection techniques used were observation, interviews, and questionnaires. The data were analyzed by simple regression with the help of SPSS22.0 software for windows. The sample used is a saturated sample that uses all members of the population as a sample of 33 people.